A REVIEW ON EXPLORING THE ANTIMICROBIAL POWER OF HERBAL PLANTS - Chahna Patel; Dr. Neha Tiwari; Dr. Pragensh Patani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Traditional medicine has utilized herbal plants for centuries. In our environment, a large number of micro-organisms grow at rapid speed, which may cause harm to other living organisms and may also lead to the dangerous diseases, anti-microbial agents are used to solve this problem. The agents that kill and stop the growth of harmful microbes are known as anti-microbial agents. There are two types of antimicrobial agents include synthetic agents and herbal plants. Synthetic drugs are used as antimicrobial agents but they have various side effects like reactive oxygen species and antibiotic resistance. Herbal plants have fewer side effects than synthetic drugs. Plants have active chemical constituents that provide pharmacological action. This review provides a comparative analysis of ten herbal plants that possess anti-microbial activity. Herbal anti-microbial agent include Aloe vera (Aloe barbadensis miller), Basil (Ocimum basilicum), Clove (Syzygium aromaticum), Cinnamon (Cinnamomum verum and Cinnamomum zeylanicum), Chamomile (Matricaria chamomilla), Dill (Anethum graveolens), Mint (Mentha), Garlic (Allium sativum), Ginger (Zingiber officinale roscoe) and Lemon balm (Melissa officinalis) all of these have been summarized.